Carboxyl-terminal domain of the Epstein-Barr virus nuclear antigen is highly immunogenic in man. - Milman, G (1985)
The carboxyl-terminal one-third of the Epstein-Barr virus nuclear antigen (EBNA-1) encoded by the BamHI restriction fragment K was synthesized in Escherichia coli by use of a high-expression plasmid. The resultant 28-kDa EBNA fusion polypeptide, comprising 5-10% of the total soluble bacterial protein, was purified to apparent homogeneity by phosphocellulose and hydroxylapatite column chromatography. Both rabbit monospecific antibodies and mouse monoclonal antibodies against 28-kDa EBNA gave nuclear immunofluorescence staining on Epstein-Barr virus (EBV)-infected lymphoblastoid cell lines and recognized the appropriate intact EBNA polypeptide bands on immunoblots. An ELISA with the purified 28-kDa EBNA as antigen was used to quantitate anti-EBNA antibody in human serum samples. The ELISA method was approximately 100-fold more sensitive than the classical anticomplement immunofluorescence assay. Anti-EBNA antibody was detected in sera from 100% of normal individuals who were seropositive for the viral capsid antigen, and low anti-EBNA titers were detected in serum from most patients with acute infectious mononucleosis. The assay gave the expected pattern of titers in sera from patients with rheumatoid arthritis, Burkitt lymphoma, or nasopharyngeal carcinoma, thus confirming the validity of this purified reagent for assessing EBNA antibody status. Approximately 10% of normal individuals and rheumatoid arthritis patients had anti-EBNA titers as high as those seen in nasopharyngeal carcinoma patients. In these high-titer individuals, greater than 1% of the total IgG are antibodies that recognize 28-kDa EBNA, which indicates that the carboxyl-terminal domain of EBNA is highly immunogenic.